Penyuluhan Strategi 7P dalam Rangka Peningkatan Omset Usaha Klinik Kecantikan di Pekanbaru - Ulfah, Mutia; Anggraini, Nia; Saputri, Marlinda; Nefrida, Nefrida; Darnilawati, Darnilawati (ISEI Cabang Pekanbaru, Koordinator Provinsi Riau, 2023)
Service activities are based on the need for marketing mix formulation counseling to increase business turnover in new businesses. Referring to the conditions in the field, it is necessary to provide solutions in the form of training, counseling and discussions involving the clinical management and all of its employees to provide enlightenment, understanding, guidance and development of business potential. This training is expected to complement the knowledge and skills of the management and employees of beauty clinics in Pekanbaru in implementing various strategies that can be used to increase business turnover. The first session includes counseling on marketing mix theory (7P Marketing Mix). The second session includes counseling on Segmenting, Targeting, Positioning. The third session includes counseling about marketing strategies. The fourth session includes counseling on business management. With the completion of this service, participants can create a good marketing strategy to be able to increase the turnover of the beauty clinic business.